Análises in situ por ablação a laser ICP-MS em óxidos de ferro e estudos mineralógicos, petrográficos e geoquímicos em itabiritos e veios do depósito Serra do Sapo, MG - Marco Aurelio Maia Teodoro (2018)
In situ analyses by laser ablation ICP-MS in Fe oxides and the mineralogical, petrographic and geochemical studies allowed the understanding of the characteristics of Serra-do-Sapo-iron-deposit rocks. Located on the eastern border of southern Serra do Espinhaço, the deposit is hosted by of metamorphosed banded iron formation (BIFs) and associated quartz-and-hematite veins. Petrographic studies by optical microscopy in BIF, quartz-and-hematite veins, and quartzite allowed identification of assemblages of different iron-bearing minerals in order to individualize them by morphological and textural feature relationships, which showed the following evolution: magnetite kenomagnetite martite tabular hematite specular hematite. The latter, specifically, is associated with quartz- veins. Muscovite, chlorite, zircon, and apatite are also observed. In addition, structures such as compositional banding, which is typical in this rock, lamination, microfolds, and veinlets are identified. X-ray diffraction (XRD) analysis confirms the main mineralogy, although it does not allow the morphology distinction. The cluster analysis allowed the sample partition with similar patterns and the indication of samples with characteristic behavior. The whole rock geochemistry studies show rocks composed especially of SiO2 and Fe2O3, depending on the analysis, and less by Al2O3 and K2O. High contents of Ba and Zr in some samples also are important. The results of rare earth elements (REE) show typical patterns for BIFs, with few exceptions, both normalized to Post-Archean Australian Shale (PAAS), and Chondrite. These results suggest that there was no strong detrital contamination, although some samples show characteristics such as the presence of zircon and sedimentary structure. On the other hand, the hydrothermal influence on the samples can be verified in different diagrams. Mineral chemistry analyses by the technique of Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS), which was carried out on iron oxides, indicate variation in the trace element contents, in conformity with the observed transitions by petrography. Rare earth elements results show enrichment of light REE (LREE) contents from kenomagnetite to martite, and decrease of heavy REE (HREE) contents. In the martite tabular hematite transition is observed depletion of LREE and HREE. Specular hematite presents a different behavior for several elements, such as Ti, Al, and REE, with lower contents than the other mineral phases. Furthermore, the results of in situ analyses in minerals have features that indicate the iron-minerals genesis with hydrothermal influence, ratify the mineral paragenetic sequence indicated by petrography and still suggest a chemistry of these fluids. The obtained results, compared to studies of fluid inclusion (FI) of the literature realized in the Serra do Sapo deposit, show that the hydrothermal fluids, which is responsible for the mineral genesis, have an igneous influence, with temperature above the submagmatic temperature.